Influence of stress factors on the vital signs of neonates under intensive care - Barbosa, Robson Ourives; Emmanouilidis, Alessandra; da Silva, Andrea Lúcia Gonçalves; Fleig, Tania Cristina Malezan; Silva, Carolina Barbosa; Cardoso, Dannuey Machado (Revista de Epidemiologia e Controle de Infecção, 2020)
Background and Objectives: Maintenance of regular development and maturation of the Central Neural System of neonates in the first year of life, associated to the environmental conditions in which they are inserted, justifies the scientific relevance of this research. Our objective is to describe the influence of stress factors on hospitalized neonates in the Neonatal Intensive Care Unit of a teaching hospital. Methods: Cross-sectional study with convenience sampling. The participants were observed in moments that were identified as being of highest and lowest exposition to stress factors, thus sound pressure, illuminance, quantity of procedures, presence of pain, and the indicators of vital signs expressed by the patients’ monitors were registered. Results: Thirteen neonates, predominantly moderate premature babies of low weight, of c-section birth, average age of 8.0 ± 5.9 days, mostly female and breathing room air, were evaluated. We noted that stress factors produced significant increase of the heart rate (sound pressure: p=0.001, illuminance: p